Aminopeptidase B can bioconvert L-type amino acid transporter 1 (LAT1)-utilizing amide prodrugs in the brain - Hugele, Agathe; Löffler, Susanne; Molina, Belén Hernández; Guillon, Melina; Montaser, Ahmed B.; Auriola, Seppo; Huttunen, Kristiina M. (Frontiers in Pharmacology, 2022)
A prodrug approach is a powerful method to temporarily change the physicochemical and thus, pharmacokinetic properties of drugs. However, in site-selective targeted prodrug delivery, tissue or cell-specific bioconverting enzyme is needed to be utilized to release the active parent drug at a particular location. Unfortunately, ubiquitously expressed enzymes, such as phosphatases and carboxylesterases are well used in phosphate and ester prodrug applications, but less is known about enzymes selectively expressed, e.g., in the brain and enzymes that can hydrolyze more stable prodrug bonds, such as amides and carbamates. In the present study, L-type amino acid transporter1 (LAT1)-utilizing amide prodrugs bioconverting enzyme was identified by gradually exploring the environment and possible determinants, such as pH and metal ions, that affect amide prodrug hydrolysis. Based on inducement by cobalt ions and slightly elevated pH (8.5) as well as localization in plasma, liver, and particularly in the brain, aminopeptidase B was proposed to be responsible for the bioconversion of the majority of the studied amino acid amide prodrugs. However, this enzyme hydrolyzed only those prodrugs that contained an aromatic promoiety (L-Phe), while leaving the aliphatic promoeities (L-Lys) and the smallest prodrug (with L-Phe promoiety) intact. Moreover, the parent drugs’ structure (flexibility and the number of aromatic rings) largely affected the bioconversion rate. It was also noticed in this study, that there were species differences in the bioconversion rate by aminopeptidase B (rodents > human), although the in vitro – in vivo correlation of the studied prodrugs was relatively accurate.